The Mitochondrial Voltage-Dependent Anion Channel 1, Ca2+ Transport, Apoptosis, and Their Regulation - Shoshan-Barmatz, Varda; De, Soumasree; Meir, Alon (Frontiers in Oncology, 2017)
In the outer mitochondrial membrane (OMM), the voltage-dependent anion channel 1 (VDAC1) functions in cellular Ca2+ homeostasis by mediating the transport of Ca2+ in and out of mitochondria. VDAC1 is highly Ca2+-permeable and modulates Ca2+ access to the mitochondrial inter-membrane space. Intra-mitochondrial Ca2+ controls energy metabolism by enhancing the rate of NADH production via modulating critical enzymes in the tricarboxylic acid (TCA) cycle and fatty acid oxidation. Mitochondrial [Ca2‏+] is regarded as an important determinant of cell sensitivity to apoptotic stimuli and was proposed to act as a ‘priming signal’, sensitizing the organelle and promoting the release of pro-apoptotic proteins. However, the precise mechanism by which intracellular Ca2+ ([Ca2+]i) mediates apoptosis is not known. Here, we review the roles of VDAC1 in mitochondrial Ca2+ homeostasis and in apoptosis. Accumulated evidence shows that apoptosis-inducing agents act by increasing [Ca2+]i and that this, in turn, augments VDAC1 expression levels. Thus, a new concept of how increased [Ca2+]i activates apoptosis is postulated. Specifically, increased [Ca2+]i enhances VDAC1 expression levels, followed by VDAC1 oligomerization, cytochrome c release and subsequently, apoptosis. Evidence supporting this new model suggesting that up-regulation of VDAC1 expression constitutes a major mechanism by which apoptotic stimuli induce apoptosis, with VDAC1 oligomerization being a molecular focal point in apoptosis regulation is presented. A new proposed mechanism of pro-apoptotic drug action, namely Ca2+-dependent enhancement of VDAC1 expression, provides a platform for developing a new class of anti-cancer drugs modulating VDAC1 levels via the promoter, and for overcoming the resistance of cancer cells to chemotherapy.